Efektifitas Pengelolaan Dana Zakat pada Program Pendidikan di Bazna Kota Bima - Mujnah; Umar Sagaf; Muh Yunan Putra (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
This study aims to determine the effectiveness of zakat fund management in education programs run by BAZNAS Kota Bima. This study uses a descriptive qualitative approach with data collection techniques through interviews, observations, and documentation. The results of the study indicate that zakat fund management in education programs has been implemented effectively through systematic planning, transparent implementation, and continuous monitoring and evaluation. Education programs include scholarships, school supplies assistance, and skills training. Although there are several obstacles such as limited funds and a less than optimal mustahik data system, BAZNAS Kota Bima is able to overcome them with innovation and cross-sector collaboration.